Integration of Universities and Employers – Potential in Building Social Capital - S. M. Apenko; A. V. Lukash; A. I. Davydov (Высшее образование в России)
The article analyzes the main directions of integration of universities and employers, considered in the context of formation of social capital of participants of educational relations. The empirical basis of the work was formed by: 1) data on self-evaluation for 2023 of four leading universities of the Omsk region, differing in the structure of educational programs and industry focus (OmSTU, OmSU, OmGUPS, SibADI); 2) the results of questionnaire survey of the main participants of the educational process: students and employers of these universities; 3) data from the survey of university youth within the framework of the Federal project “Runway 2023” (2,139 students of these universities). The novelty of the study lies in the substantiation of the practices of integration of universities and employers that have developed in the educational environment as ways of reproducing social capital for the key participants of educational relations. These practices contribute to the establishment of trust between the participants of educational relations; form communications that become resources for obtaining benefits for the parties involved in cooperation; help students to master the corporate norms and rules of employers; reduce the level of transaction costs in employment, etc. It has been established that the main forms of integration of universities and their partners are realized mainly to achieve a high level of postgraduate employment of graduates, which in practice are associated with the reproduction of social capital of both open and closed type. Based on the analyzed sources, the following hypotheses were confirmed: firstly, representatives of employers who have experience of cooperation with universities are more likely to prefer to use and develop such formats of integration with educational organizations that are focused on solving the problems of youth employment, i.e. they use the accumulated social capital to build up the human capital of their organizations; secondly, the level of students’ readiness to recommend an educational organization for admission and graduation. The authors show promising directions of research on the subject of the article: 1) the establishment of system-wide and industry barriers that impede the development of bridging social capital for the production of an innovative product; 2) a comprehensive analysis of bridging social capital, which reflects the quality of communication and cooperation in the context of personal responsibility and competencies of officials of both participants in the educational process.